Evaluation of Protective Clothing against Chemical and Fire Hazards : Evaluation of Protective Clothing against Chemical and Fire Hazards - Mehreen Ijaz, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Workplace accidents are very unpredictable. Protection against these risks and hazards is of utmost importance in every profession. Clothing has always been considered one of the integral parts of personal protective equipment. The present study aims at manufacturing and evaluating protective clothing materials used by chemical workers. It was experimental. Two important resistance characteristics; chemical and fire were assessed against international performance standards. The results highlighted the fact that the right selection of construction parameters was able to make a safe fabric against such hazards. The resultant fabric was evaluated at various washing intervals and was found to be resistant to four selected chemicals through penetration and repellency index. It was also able to resist fire by passing the standard after flame and char length tests. Very little research work has been done in Pakistan regarding the manufacturing and physical assessment of clothing materials used by chemical workers. This study aimed to approach the target area where the protection and safety of the worker should be a priority.